2018
DOI: 10.7554/elife.31326
|View full text |Cite
|
Sign up to set email alerts
|

Endosomal Rab cycles regulate Parkin-mediated mitophagy

Abstract: Damaged mitochondria are selectively eliminated by mitophagy. Parkin and PINK1, gene products mutated in familial Parkinson’s disease, play essential roles in mitophagy through ubiquitination of mitochondria. Cargo ubiquitination by E3 ubiquitin ligase Parkin is important to trigger selective autophagy. Although autophagy receptors recruit LC3-labeled autophagic membranes onto damaged mitochondria, how other essential autophagy units such as ATG9A-integrated vesicles are recruited remains unclear. Here, using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
115
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 65 publications
13
115
0
Order By: Relevance
“…ing C-I30 mRNP to OMM, cotranslational quality control factors and autophagy receptors to OMM-associated mRNPs, to the subsequent activation of mitophagy, could occur in the absence of Parkin. This contrasts the prevailing view that the activation of Parkin and subsequent ubiquitination of a battery of Parkin substrates on MOM is essential for PINK1-activated mitophagy 120. Consistent with previous studies, our results indicated that though not required, the presence of Parkin provides an amplifying mechanism to promote PINK1-directed mitophagy, as both the recruitment of autophagy receptors and the clearance of damaged mitochondria are accelerated in the presence of Parkin.…”
supporting
confidence: 84%
“…ing C-I30 mRNP to OMM, cotranslational quality control factors and autophagy receptors to OMM-associated mRNPs, to the subsequent activation of mitophagy, could occur in the absence of Parkin. This contrasts the prevailing view that the activation of Parkin and subsequent ubiquitination of a battery of Parkin substrates on MOM is essential for PINK1-activated mitophagy 120. Consistent with previous studies, our results indicated that though not required, the presence of Parkin provides an amplifying mechanism to promote PINK1-directed mitophagy, as both the recruitment of autophagy receptors and the clearance of damaged mitochondria are accelerated in the presence of Parkin.…”
supporting
confidence: 84%
“…Another interesting candidate to relay the depolarization signal might be the protein kinase PINK1, which is stabilized on the outer mitochondrial membrane (OMM) of depolarized mitochondria (Narendra et al, 2010). An important role of PINK1 is to initiate PARKIN-mediated mitophagy by phosphorylating both PARKIN and ubiquitin (Okatsu et al, 2013;Pickles et al, 2018;Yamano et al, 2018). PINK1 is expressed in U2OS cells (McLelland et al, 2018) while PARKIN has not been detected (Durcan et al, 2014), so it is possible that stabilized PINK1 phosphorylates other substrates that control Arp2/3 complex activation.…”
Section: Discussionmentioning
confidence: 99%
“…Mitofusin2 (MFN2), which is degraded by the proteasome following mitochondrial depolarization [22], underwent rapid degradation within 3 h of valinomycin treatment ( Fig 2D and E), in particular the mitochondria-rich fractions. MTCO2, an inner mitochondrial protein that is degraded via mitophagy following mitochondrial depolarization [40], was significantly decreased following 24 h of valinomycin treatment ( Fig 2D and E). In contrast, 3Flag-MITOL persisted throughout the first 6 h and only underwent a slight reduction after 24 h, confirming that the total cellular amount of MITOL is not dramatically decreased.…”
Section: Mitol Redistributes To Peroxisomes In Response To Mitochondrmentioning
confidence: 96%